Action & cut: Using Windows Movie Maker XP® in ESL classrooms - Ali, Zuraina (Faculty of Communication and Modern Languages, Universiti Utara Malaysia, 2007)
This study looks at the use of Windows Movie Maker XP® to facilitate students' presentation skills in their English for Professional Communication classes. In the study, students are given the task to produce a short movie based on their meeting presentations which contribute 10% to their course assessment. They are instructed to form groups which consist of five to six members. The movie has to be approximately 10 minutes long with the script written originally by the students. They also need to submit the completed version of the movie in a CD format. The study indicates that Windows Movie Maker XP® enables students to share their meeting presentation movies with their classmates and lecturers. This study also shows that using Windows Movie Maker XP® can help students' learning environment in many ways: they find that English as a Second Language (ESL) classrooms can be enjoyable because of the availability of technology which they can utilize; they improve their English in the context of meeting environments which are assigned by their lecturers, and they build their confidence through the role play.